Effect of Everolimus-Coated Ureteral Stent on Ureteral Anastomosis and Renal Ischemia-Reperfusion Damage: A Rabbit Experimental Model - Fatih Sandikci; Alihan Kokurcan; Sanem Cimen Guler; Sertac Cimen; Tugba Taskin Turkmenoglu; Fevzi Nuri Aydin; M. Abdurrahim Imamoglu (International Journal of Clinical Practice)
Conclusion: We conclude that everolimus has the potential to prevent ureteral strictures.